The Impact of Metacognition on Elementary School Students’ Problem-Solving Skills in Science Learning - Fauziana Fauziana; Sarah Fazilla (Universitas Pendidikan Ganesha, 2022)
The concept of education at the basic education level plays an important role in character building and students' cognitive, affective, and psychomotor development. Through science learning, it is hoped that students will not only know the concept, but are directed to be able to solve problems in the surrounding environment. However, the facts show that students in elementary schools still have difficulty solving analytical problems in science learning. This study aims to analyze the effect of metacognition on the ability to solve science problems in fifth grade elementary school students. The method used in this study is a quantitative method. The sample in this study were 50 grade 5 students, who were selected using a random sampling technique. Data was collected using an instrument in the form of a questionnaire. The data analysis method used is simple linear regression analysis. The results showed that the value of tcount was greater than ttable, namely 3,086 > 2,312 at a significance level of = 0.05. Thus, it can be concluded that there is a significant effect of metacognition on the ability to solve science problems. The implications of the results of this study are expected to be used as evaluation material and input for teachers in choosing and using appropriate learning strategies so as to improve problem-solving skills in science learning at the elementary school level.